Influence of floor type on production performance and worm load in lactating Jakhrana goats - RAMACHANDRAN, N; SINGH, S P; POUROUCHOTTAMANE, R; SHARMA, D K; BHUSAN, S; RAI, B; JINDAL, S K (The Indian Journal of Animal Sciences, 2019)
The aim of this study was to investigate the effect of slatted floor (SLF) over soil floor (SOF) on performance of lactating goats reared under group feeding conditions up to 120 days postpartum. Fortnightly live weight and weekly test day milk yield was recorded and milk yield was calculated for 30, 60, 90 and 120 days postpartum. Worm load of goats were assessed. Milk yield was significantly lower at 30 days, showed lower trend at 60 days and at 90 days postpartum in SLF than SOF. The overall milk yield in SLF and SOF were 1.114Â±0.12 and 1.358Â±0.12 l/goat/day, respectively. The coccidial oocysts in SLF goats were non-significantly lower, tapeworms and roundworms were similar than that of SOF goats.